TANGGAPAN MAHASISWA TERHADAP KUALITAS PELATIHAN PENELITIAN TINDAKAN KELAS - Endang Sumarti; Harun Ahmad Sangaji; Yahmun Yahmun (linguistic, literature, and teaching, 2019)
This research is motivated by the desire to find out the responses of the traineesto the quality of classroom action research (PTK) training conducted by IKIP Budi Utomo Malang. For that reason, the three research questions were proposed, namely first, how are the trainees' responses to the trainers’ competency? Second, how are the trainees’ understandingof the training material? Third, how are the trainees’ responsesto the quality of training? Data collection uses questionnaires, then analyzed by descriptive techniques, and the results are as follows. First, trainees' responses to trainers’ competencyare in Good category. This is evidenced by the average oftrainees’ answers in the range above 70% of interval scale, concerning skills competency, material delivery, giving instructions, and trainees’ responses. Second, the trainees' understanding of the training material is quite sufficient, because it is in the range 40% of interval scale. This is caused by many factors, even though the competence of the trainers have met the standards of feasibility. Third, the quality of the training is included in the Good category, because 71% of 100 trainees stated Good. This shows that the performance of the training has reached a feasiblestandard.